2010
DOI: 10.1007/dcr.0b013e3181f0869f
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Flap Coverage for Chronic Anal Fissure: Lower Incidence of Anal Incontinence Compared to Lateral Internal Sphincterotomy After Long-Term Follow-up

Abstract: Long-term follow-up shows a very low incidence of mild anal incontinence after dermal flap coverage. We conclude from this study that the dermal flap procedure appears to be efficacious without an increased risk of incontinence and with results comparable to lateral internal sphincterotomy. The dermal flap procedure can be recommended for patients following failed conservative fissure treatment without the potential risk of anal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The results obtained have been good; in particular, a high healing rate, reduced incidence of complications and recurrences and complete preservation of anal continence have been reported. In patients with dermal flap, Hancke et al [36] in a comparative study between dermal flap coverage and lateral internal sphincterotomy reported a significant reduction of anal incontinence. However, to date published reports have been based only on a small sample size; only one study published in 1970 analysed a high number of procedures [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained have been good; in particular, a high healing rate, reduced incidence of complications and recurrences and complete preservation of anal continence have been reported. In patients with dermal flap, Hancke et al [36] in a comparative study between dermal flap coverage and lateral internal sphincterotomy reported a significant reduction of anal incontinence. However, to date published reports have been based only on a small sample size; only one study published in 1970 analysed a high number of procedures [35].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of advancing flaps of skin and fat is based on introducing fresh blood supply to the ischaemic area of the fissure [2], reducing the time required for perianal wound healing and avoiding the risk of anal stenosis that follows healing by scarring [16]. This procedure has been performed selectively on patients with CAF without hypertonia of IAS [5,6,[31][32][33] or extensively, independently of CAF side and sphincter tone [13,14,[34][35][36]. The results obtained have been good; in particular, a high healing rate, reduced incidence of complications and recurrences and complete preservation of anal continence have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Patient motivation, counseling of risks involved with treatment options available, and the ability to deliver a package of treatment options, including undertaking an anal advancement flaps, determine which steps are available to minimize the need for sphincter division, thereby keeping the risks of incontinence to a minimum [16]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of fissurectomy reported here compare favourably with those after LIS. As can be seen in Table 2, in two of the three sphincterotomy studies fewer patients (33% and 47.7%) were perfectly continent postoperatively [22,23]. In the third study almost 90% of patients were perfectly continent but the duration of follow‐up was unclear [24].…”
Section: Discussionmentioning
confidence: 99%